Steroids in the treatment of IgA nephropathy to the improvement of renal survival: a systematic review and meta-analysis. - Yu-Hao Zhou; Li-Gong Tang; Shi-Lei Guo; Zhi-Chao Jin; Mei-Jing Wu; Jia-Jie Zang; Jin-Fang Xu; Chun-Fang Wu; Ying-Yi Qin; Qing Cai; Qing-Bin Gao; Shan-Shan Zhang; et al. (PLoS ONE)
Background Studies have shown that steroids can improve kidney survival and decrease the risk of proteinuria in patients with Immunoglobulin A nephropathy, but the overall benefit of steroids in the treatment of Immunoglobulin A nephropathy remains controversial. The aim of this study was to evaluate the benefits and risks of steroids for renal survival in adults with Immunoglobulin A nephropathy. Methodology and principal findings We searched the Cochrane Renal Group Specialized Register, Cochrane Controlled Trial Registry, MEDLINE and EMBASE databases. All eligible studies were measuring at least one of the following outcomes: end-stage renal failure, doubling of serum creatinine and urinary protein excretion. Fifteen relevant trials (n = 1542) that met our inclusion criteria were identified. In a pooled analysis, steroid therapy was associated with statistically significant reduction of the risk in end-stage renal failure (RR: 0.46, 95% CI: 0.27 to 0.79), doubling of serum creatinine (RR = 0.34, 95%CI = 0.15 to 0.77) and reduced urinary protein excretion (MD = -0.47 g/day, 95%CI = -0.64 to -0.31). Conclusions/significance We identified that steroid therapy was associated with a decrease of proteinuria and with a statistically significant reduction of the risk in end-stage renal failure. Moreover, subgroup analysis also suggested that long-term steroid therapy had a higher efficiency than standard and short term therapy.